DEVELOPMENT OF INQUIRY-BASED LEARNING ACTIVITIES TO PROMOTE ANALYTICAL THINKING IN HEALTH EDUCATION COURSE FOR MATHAYOMSUKSA 5 STUDENTS - Kwangmuang, Kwansiri; Saengngam, Kanyawadee (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The research aims to promote analytical thinking health education course For Mathayomsuksa 5 students who received a 5-step quest for knowledge learning management, the target group were students in Mathayomsuksa 5 School, Wang Luang Wittayakhom School, Wang Luang Subdistrict. Selaphum District, Roi Et Province, in the first semester of the academic year 2021, consisted of 21 students. The research instruments were 1) a learning management plan using the 5-step knowledge-seeking model, and 2) an analytical thinking ability scale. The learning outcomes of Mathayomsuksa 5 students were conducted using a 5-step quest for knowledge. The statistics used in the data analysis were mean, percentage, standard deviation. and Wilcoxon signed ranks test. The results of the research were as follows: 1. The effectiveness of the 5-step inquiry-based learning management plan to promote critical thinking in health education subjects. For students in Mathayomsuksa 5 with efficiency 82.38/84.92 which is higher than the criteria set 80/80 2. The results of the comparison of analytical thinking in health education subjects. For students in the Mathayomsuksa 5 of junior high school, there are scores from taking the analytical thinking test in health education subjects. The students who received knowledge-seeking learning management, 5 steps, 30 questions before and after learning, had a total score of 364 and 535, with an average of 17.33 and 25.48 There were standard deviations of 1.21 and 1.76, representing a percentage. 57.78 and 84.92 respectively.